Characteristics of Briquettes Made from Plastic Waste, Plastic-Coconut Shell Blends, and Plastic-Corn Cob Composites - Djola, Wiwin Iswandi; Prasetyo, Dhimas Mardyanto; Salsabila, Nandita Pasya; Sadir , Muhammad; Hidayati, Eni (Jurnal Pijar Mipa, 2025)
Recycling plastic waste holds considerable potential as a fuel source, especially when combined with agricultural waste. This study aims to evaluate the physical characteristics of charcoal briquettes - moisture content, ash content, volatile matter, calorific value, and fixed carbon content - produced from a mixture of plastic waste and organic waste. Three composition variations were tested: pure Low Density Polyethylene (LDPE) plastic waste (100%) as the first treatment (S1), a combination of coconut shells and plastic waste in a 50%:50% ratio as the second treatment (S2), and a combination of corn cobs and plastic waste in the same 50%:50% ratio as the third treatment (S3). Testing was conducted according to SNI 01-6235-2000 standards. The results showed that all treatments produced charcoal briquettes with moisture content and calorific value that met SNI standards. Among the treatments, briquettes made entirely from plastic waste (S1) achieved the highest calorific value at 5921 cal/g, followed by the plastic-coconut shell mixture (S2) at 5574 cal/g and the plastic-corn cob mixture (S3) at 5100 cal/g. These findings indicate that plastic waste and agricultural waste have significant potential as fuel sources for power generation, supporting energy mix targets, and contributing to waste management and sustainable energy production. However, the study also identified areas for improvement. The ash content across all treatments failed to meet SNI standards, and the volatile matter content in S1 was below the acceptable range. These shortcomings highlight the need for further optimization in material formulation and manufacturing processes to enhance briquette quality. Future research should prioritize refining material combinations, improving ash content and volatile matter characteristics, and assessing the environmental impacts of using plastic-based briquettes. With continued innovation, this approach could play a pivotal role in achieving energy mix targets and addressing the challenges of plastic and agricultural waste, offering a sustainable and practical solution for energy generation.